Různá pojetí endogenity peněz v postkeynesovské ekonomii: Reinterpretace do obecnější teorie - Ondřej Lopušník (Charles University in Prague, Institute of Economic Studies (IES), 2010)
– The theory of endogenous money supply forms one of the cornerstones of Post Keynesian economics. It has been developing rapidly during the last twenty years, but is still neglected as a theoretical background for practical central bank policy. This may be (among other reasons) due to the existence of different approaches to money endogeneity within Post Keynesian economics. Post Keynesian economics hus lacks a general formulation of money endogeneity. Naturally, one may ask whether reinterpretation of current approaches to endogeneity - structuralism and horizontalism - into more general theoretical framework is possible. This paper aims at finding an answer to this question. Two approaches to reinterpreting structuralism and horizontalism into more general theoretical framework are identified and discussed. Despite some progress in this area, however, the paper argues that a general formulation of money supply endogeneity is still an impossibility.
Keywords: B50; E12; E51; 330; Post Keynesian economics; Money supply; Structuralism; Horizontalism; Postkeynesianismus; Geldmenge; Strukturalismus; Theorie